جهود المالكية في تجديد صيغ عقود الاستثمار وتطويرها: التمويل بالمزارعة نموذجا Maliki’s Effort in Renewing and Developing Formulas of Investment Contracts: A case study of Financing with agriculture (Muzara’ah) - Edris, Mahmoud Mohamed Ali Mahmoud (International Journal of Al-Turath In Islamic Wealth and Finance, 2020)
تهدف هذه الدراسة إلى إبراز دور فقهاء السادة المالكية في تجديد منتجات التمويل الإسلامي الشبيهة بالمضاربة والمشاركة والمتمثلة في صيغ المزارعة، والمغارسة والمساقاة وتطويرها ونفض الغبار عنها لبيان ما تزخر به كتب فقهاء المذهب المالكي، بوصفها صيغَ عقودٍ ناجحة للاستثمار في تمويل مشروعات الفلاحة المنتجة. انطلاقًا مما تناوله الفقهاء ستكشف الورقة للقارئ أساليب الصيغ الثلاثة وهي: المزارعة، والمغارسة والمساقاة بنوع من التفصيل المبين والمفيد. وتناولت الدراسة أهمية بوصفها قطاعًا اقتصاديًّا استراتيجيًّا لما له من دور بارز في توفير الغذاء للإنسانية، حيث يشكّل الركيزة الأساسية في التنمية الاقتصادية، ويُحدث تغييرًا حقيقيًّا لحالة العوز المستشرية في المجتمعات المسلمة وكذلك يرفع من مكانة الدول التي تعتني وتقوم على تنميته من خلال توفير مصادر المال، والمياه والأراضي وهو القطاع الذي أعرض عنه كثير من الباحثين، ولم يحظَ بقدر من الاهتمام به اهتمامًا كافيّا. وستوضّح الدراسة اختلافات آراء الفقهاء حول مشروعية العمل بصيغ المزارعة، والمغارسة والمساقاة وشروطهم مركّزة على آراء المذهب المالكي. ولترتيب الورقة تكون الدراسة ضمن محورين رئيسين:المحور الأول: يتناول جهود فقهاء المالكية في تجديدهم لصيغ عقود الاستثمار التمويلي وتطويره بما يتواكب مع واقعنا المعاصر. المحور الثاني: مشروعية العمل بأساليب الصيغ الثلاثة المتمثلة في المزارعة، والمغارسة والمساقاة، مبينًا اختلافات وجهات نظر الفقهاء حولها وإيجابياتها المتوقعة في تمويل المشروعات الفلاحية. وستختتم الدراسة بأهم النتائج والتي يتوقّع أن تكون إضافة جديدة للورقة. وسوف تعتمد الدراسة في تعاطيها لاجتهادات فقهاء السادة المالكية وتجديدهم لصيغ التمويل بالمزارعة، والمغارسة والمساقاة من خلال المنهج الوصفي التحليلي. Abstract This study aims to highlight the role of Maliki jurists in the renewal of Islamic finance products similar to Mudarabahand partnership which are in the form of Muzara’ah, Mugarasah, and Musaqah. These contracts are evidence that Maliki Books have contributed immensely to the development of agricultural projects. The paper aims to reveal to reader the three forms namely Muzara’ah, Mugarasah and Musaqah in an interesting and detailed manner. The study discloses the importance of agriculture as a strategic economic sector, but it was not given sufficient attention, which may bring about a real change in the destitution situation prevalent in Muslim societies, as well as the position of the countries that care and build on its development by providing sources of money, water and land. The study will clarify the differences of opinions of jurists on the legality of Muzara’ah, Mugarasah and Musaqah and their conditions, focusing on the opinions of the Maliki School. To arrange the paper, the study is based on two main axes: First Axis: Deals with the efforts of the Maliki jurists in renewing the formulas of financing investment contracts and developing them in line with our contemporary reality. Second Axis: Deals with the legality of working in the three formulas methods represented in Muzara’ah, Mugarasah and Musaqah indicating the differences of views of jurists about it and its expected positives in financing agricultural projects. The study will conclude with the most important results, which are expected to be a new addition to the paper. The study will adopt descriptive analytical method. Key words: Efforts, Maliki, Renewal, Formulas, Contracts, Investment, Financing, Agriculture.